2016
DOI: 10.1089/jpm.2016.0174
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Symptom Experience in Head and Neck Cancer Patients with Lymphedema

Abstract: Clinicians need to inquire about tissue swelling and associated symptoms early in the post-treatment period to initiate lymphedema management strategies in a timely manner and facilitate reduction of long-term symptom burden and functional deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…These findings offer support for the notion that HNL in the oral cavity may further impair the functioning of the structures used in articulation (Lewin et al., ). The findings are also consistent with a small number of studies that have noted patient‐reported speech imprecision and unintelligibility in patients who experience HNL (Deng, Ridner, Murphy et al., ; Deng et al., ; Piso et al., ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These findings offer support for the notion that HNL in the oral cavity may further impair the functioning of the structures used in articulation (Lewin et al., ). The findings are also consistent with a small number of studies that have noted patient‐reported speech imprecision and unintelligibility in patients who experience HNL (Deng, Ridner, Murphy et al., ; Deng et al., ; Piso et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…Feelings of tightness, heaviness and feeling swollen on the external face and neck were highlighted, which is consistent with previous research (Deng, Ridner, Murphy et al., ; Deng et al., ; McGarvey et al., ). The vast majority also described altered sensation in relation to the presence of internal HNL, which has also been previously documented (Deng et al., ). The presence of altered sensation is often one of the first symptoms described by patients with HNL (Smith & Lewin, ).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations